PERENCANAAN DAN PENJADWALAN DISTRIBUSI USAHAUSAHA KONVEKSI DARI IKM DM MENGGUNAKAN METODE DISTRIBUTION RESOURCE PLANNING - Syarif Hidayat; Devi Utami Agustini; Nunung Nurhasanah; Ajeng Putri (JURNAL TEKNIK INDUSTRI, 2014)
In the face of free markets in Asia that will occur by 2015, many companies areworking to improve and enhance all aspects of its business. One improvement in terms ofthe distribution system. IKM DM is a company engaged in the business of producingapparel office for women. IKM DM does not have a location for the manufacture of itsproducts but the company has a partner that is 11 business locations convection whichhelps in the production activities of the company. The company currently has notimplemented the planning of the number of units that should be in the order ofdistribution and scheduling each period for each attempt of convection. Recently,planning process only be conducted based on instinct of management and to the scheduleundetermined. Every convection only be given a time limit the delivery of goods so to thewarehouse IKM DM.This research focuses on the planning and scheduling distribution efforts ofconvection became a partner of the IKM DM using the Distribution Resource Planning(DRP) and this study only deals with products of office trousers of IKM DM. Convectionthat produce these products there was only 5 convection, namely convection alan,bambang, kusnandi, noto, and rani. The result of the calculation of DRP shows scheduledistribution and the number of units of a product that must be submitted for each period.Based on the recapitulation for 14 period obtained the result that convection alan doorder as many as 81,438 units, convection bambang as many as 18,625 units, convectionkusnandi as many as 89,265 units, convection noto as many as 48,768 units andconvection rani as many as 60,099 units.